Study komperasi struktur ekonomi Negara ASEAN - Syaparuddin Syaparuddin; Selamet Rahmadi; Yusnita Yusnita (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2020)
This study aims to analyze: 1) changes in the economic structure of ASEAN countries; 2) comparison of the economic structure of ASEAN countries. The data used in this research is secondary data which includes 2000-2016 time-series data and 10 countries cross-sections. Based on the results of the analysis, it shows that changes in the economic structure of ASEAN countries from 2000 to 2016 fluctuated each year. It can be seen from the GDP data on the average contribution of sectors based on business fields and based on shifting sub-sectors, namely the agricultural sector, the industrial sector, and the service sector. From the economic structure of ASEAN countries apart from (Singapore) for the agricultural sector, the largest contribution was Myanmar 40.55%, and the lowest contribution was Brunei Darussalam 0.89%. For the industrial sector, the largest contribution was Brunei Darussalam 66.79%, and the lowest contribution was Myanmar 23.22%. The service sector with the largest contribution was the Philippines at 54.91%, and the lowest contribution was Brunei Darussalam 32.31%. Keywords: Leading sector, Shift-share, Economic Structure, GDP